Unveiling the Challenges Faced by Dalit Children in Community Schools of Nepal - Baraily, Khagendra; Sherpa, Dawa (Tribhuvan University Journal, 2025)
The Dalit community, one of the tribal communities, is economically exploited, educationally backwards, socially excluded, politically voiceless, psychologically dominated, marginalized, and disadvantaged in Nepal. The Dalit children are facing a myriad of challenges in acquiring education from and within school. Such sufferings range from community to school, and so far up to higher education. In this context, this study intends to explore the challenges they face in school while acquiring education from and within the community school of Nepal. Qualitative research, along with interpretative phenomenological approach, was employed in this study. A total of eight Dalit students, comprising four Madhesi Dalit (Risidev, Santal, Das, Paswan) and four Pahade Dalit (Biswokarma, Pariyar, Sarki, Gandarva) from secondary levels of community schools located in Morang district, were purposively selected as participants for this study. In depth interviews were conducted with participants via semi-structured interview guidelines. The interviews were recorded and transcribed verbatim. The thematic analysis techniques were used to analyze the data. The study revealed that the Dalit students faced several challenges, such as administrative challenges, bullying, negative labelling, underestimation, unfriendly behavior, unfair treatment and poor motivation for education. This study implicates policymakers and education planners in making a strategy for setting non-discriminatory practices in education that promotes an equitable and inclusive society.